Profil dan analisa risiko transisi pada level global - Habib, Syaiful (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: The driving factor for world transition risk is the agreement on a commitment to a net zero carbon economy in order to fulfill agreements between countries that are part of the Paris Agreement, for example levies on carbon or an emissions trading system (ETS). The four risks driving the global transition are Policy, Technology, Consumer Preferences/Market Sentiment. Transition risk has weak valuation validity because it is only based on the principles of each country's commitment, such as the Net Zero Emissions commitment in the Paris Agreement. Transition risks are systemic, for example economic sector risks that disrupt business globally, the occurrence of stranded assets, requiring wise investment, rising commodity and energy prices. The global level transition risk profile for (policies) in the primary energy mix with the NZE 2050 scenario has a greater projection of the use of New Renewable Energy/EBT for (Biomass, Wind, Hydro and Geothermal) compared to the current policy which still uses fossil energy. Methods: This research uses qualitative methods through literature analysis and literature research. Findings: The risk profile of the global (technology) transition from Global Power Generation to EBT with the Further Acceleration and Achieved Commitment (Solar, Wind Offshore and Onshore) scenarios in 2050 has a greater projected use of EBT compared to Fading Momentum and Current Trajectory. Global level Transition Risk Profile for (Investor Sentiment) in global energy sector investment with the Further Acceleration and Achieved Commitment (Power T&D, Decarbonization technology and Power|renewables) scenarios in 2050 has a projected percentage of total investment that is greater than the Fading Momentum scenario and Current Trajectory. The transition risk scores of all countries according to the Europan Investment Bank (EIB) paint a different picture. Countries that export fossil fuels are those most at risk. Conclusion: High-income countries, which consume a large share of the world's resources and produce significant emissions, generally face higher risks from the transition to a low-carbon world economy. Global risk analysis for the first impact of all driving factors (policy, technology, investor and consumer sentiment) is at a severe impact with a very close chance or probability of occurring. However, if all mitigation is carried out well and correctly, consistently and all countries fulfill the same commitments (for example, complying with the Paris Agreement commitments), then the residual impacts produced within a certain time will be small with the possibility of this occurring and a shift in the risk rating from extreme to moderate.